PENGARUH PENDEKATAN CTL TERHADAP KEMAMPUAN MENULIS PUISI SISWA KELAS V SDN 12 PONTIANAK KOTA - Dwi Resti; Siti Halidjah; Kartono Kartono (Universitas Tanjungpura, 2019)
AbstractThis study was to analyze the effect of the contextual teaching and learning approach on the ability to write poetry for V class students of the 12 Pontianak City Elementary School. The method used is an experimental method, the form of research used is quasi experimental design with nonequivalent control group design. the population and sample of this study were all students of class V. Data collection tools in the form of essay test. The results of data analysis, the average post-test experiment 74,42 while the average pos-test control 70,13. T-test results are 1,682 and ttable α = 5% (with dk = 26 + 24 - 2 = 48) of 1,679, so tcount (1,682)> ttable (1,679) then the alternative hypothesis (Ha) is accepted. It can be concluded that there is an effect of the contextual teaching and learning approach to the ability to write poetry for V class students of the 12 Elementary School in Pontianak Kota. The result of the calculation of the effect size is 0,38 ( medium criteria). This means that the contextual teaching and learning approach gives a good influence on the ability to write poetry for V class students of the 12 Elementary School Pontianak Kota.Keywords: Contextual Teaching and Learning, Poetry, Writing AbilityAbstractThis study was to analyze the effect of the contextual teaching and learning approach on the ability to write poetry for V class students of the 12 Pontianak City Elementary School. The method used is an experimental method, the form of research used is quasi experimental design with nonequivalent control group design. the population and sample of this study were all students of class V. Data collection tools in the form of essay test. The results of data analysis, the average post-test experiment 74,42 while the average pos-test control 70,13. T-test results are 1,682 and ttable α = 5% (with dk = 26 + 24 - 2 = 48) of 1,679, so tcount (1,682)> ttable (1,679) then the alternative hypothesis (Ha) is accepted. It can be concluded that there is an effect of the contextual teaching and learning approach to the ability to write poetry for V class students of the 12 Elementary School in Pontianak Kota. The result of the calculation of the effect size is 0,38 ( medium criteria). This means that the contextual teaching and learning approach gives a good influence on the ability to write poetry for V class students of the 12 Elementary School Pontianak Kota. Keywords: Contextual Teaching and Learning, Poetry, Writing Ability